(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2025)
This article covers the origin, development stages of supply chain management and its role in modern economic activity. Based on historical sources, it is emphasized that the concept of "logistics" was formed starting from the ancient Greek and Roman periods, and its initial forms were used in military and administrative activities. The presentation also highlights the importance of supply and supply chain in effectively organizing the activities of enterprises in the context of the digital economy. This serves as an important theoretical basis for developing the methodological foundations of new types of logistics services.